Analysis of Student Attitudes to Develop a Self-Assessment Model of Genre-Based Writing Class - Taufiqulloh, Taufiqulloh; Yuvita, Yuvita; Sulistianingsih, Endang (Lingua Cultura, 2018)
This research aimed to develop learners’ autonomy in English as Foreign Language (EFL) writing class, in particular, it was applying self-assessment. It enabled learners to raise their awareness in learning and to improve the goal orientation. The research also helped teachers to reduce their burdens of assessment and entailed a long-term effect on the learner’s autonomy. The objective of this research was to figure out student attitudes in developing a self-assessment model of genre-based writing class. Quantitative and qualitative analysis were utilized to draw the findings of this research. It was conducted at the English Education Department, Faculty of Teacher Training, Pancasakti University in the even semester of the academic year 2016/2017. The data were collected from a questionnaire, classroom observation, and focus group discussions. The results of this research present students’ problems, perceptions, and needs toward the teaching and learning process of genre-based writing classes attended as preliminary research to develop a self-assessment model of EFL writing.